Weed species composition and diversity in maize as affected by tillage and fertilization in the Northern steppe of Ukraine - Shevchenko Sergey; Шевченко, Сергій Михайлович; Tsyliuryk Oleksandr; Цилюрик, Олександр Іванович; Hulenko Oleksandr; Гуленко, Олександр Іванович; Derevenets-Shevchenko Kateryna; Деревенець-Шевченко, Катерина Анатоліївна; Pryshedko Nataliia; Пришедько, Наталія Олексіївна (Nicolaus Copernicus University, 2026)
The structure of weed phytocenoses in maize crops is determined by the adaptive capacity of weeds and the specific characteristics of crop area distribution in rotation systems. The main factors driving weed dominance include herbicide resistance, a broad germination range, morphological plasticity, and the presence of neotenic traits. The use of shallow non-inversion mulching tillage methods (such as chisel plowing and flat-cut loosening) in maize cultivation increases weed infestation levels by 1.4–1.8 times, necessitating additional applications of pre-emergence and post-emergence herbicides to control weeds and prevent yield reduction. Research indicates that plow tillage and chisel plowing provide a slight advantage in maize grain productivity on unfertilized soils and under fertilization with N30P30K30. This advantage arises from improved nutrient availability and reduced weed infestation levels. However, with increased nitrogen application (N60P30K30), shallow flat-cut loosening becomes more effective, yielding similar results to plow tillage and chisel plowing, thus mitigating earlier disadvantages. At low overall weed infestation levels (9.0–12.6 plants/m²), primary soil tillage methods have no significant impact on maize grain quality. The application of mineral fertilizers, particularly nitrogen, increases protein content in maize grain while reducing carbohydrate levels, particularly starch. Структура бур’янових фітоценозів у посівах кукурудзи визначається адаптивною здатністю бур’янів та особливостями розміщення культури в системах сівозмін. Основними чинниками домінування бур’янових видів є стійкість до гербіцидів, широкий діапазон проростання, морфологічна пластичність і наявність неотенічних ознак. Застосування мілких безполицевих мульчувальних способів обробітку ґрунту, зокрема чизельного обробітку та плоскорізного розпушування, у технології вирощування кукурудзи підвищує рівень забур’яненості посівів у 1,4–1,8 раза. Це зумовлює необхідність додаткового застосування ґрунтових і післясходових гербіцидів для контролювання бур’янів та запобігання зниженню врожайності. Результати досліджень свідчать, що полицевий обробіток ґрунту та чизельне розпушування забезпечують незначну перевагу за продуктивністю зерна кукурудзи на неудобреному фоні та за внесення добрив у нормі N₃₀P₃₀K₃₀. Така перевага пов’язана з поліпшенням доступності елементів живлення та зниженням рівня забур’яненості посівів. Водночас за підвищення норми азотного живлення до N₆₀P₃₀K₃₀ мілке плоскорізне розпушування стає ефективнішим і забезпечує результати, близькі до полицевого обробітку та чизельного розпушування, що частково нівелює його попередні недоліки. За низького загального рівня забур’яненості посівів, який становив 9,0–12,6 рослин/м², способи основного обробітку ґрунту не мали істотного впливу на якість зерна кукурудзи. Внесення мінеральних добрив, особливо азотних, сприяло підвищенню вмісту білка в зерні кукурудзи, водночас зменшуючи вміст вуглеводів, насамперед крохмалю.
Видовий склад і різноманіття бур’янів у посівах кукурудзи залежно від обробітку ґрунту та удобрення в умовах Північного Степу України
Keywords: maize; кукурудза; mulching tillage; мульчувальний обробіток ґрунту; weed infestation; забур’яненість; mineral fertilizers; мінеральні добрива; yield; урожайність